Quality and asset management: conceptual compatibility towards sustainable infrastructures management. (3rd April 2023) - Sousa, Vitor; Meireles, Inês
Abstract : Asset management has been gaining momentum in both academic and industry, but is it so distinct from other existing management philosophies? This research effort discusses the relation between asset and quality management, particularly for organizations managing (public) infrastructures, to highlight the similarities and differences between both and their role towards sustainable infrastructure development. The compatibility matrix developed demonstrates that, in conceptual terms, asset and quality management are highly similar in the scope of these organizations. As such, organizations implementing formal and certified asset management systems should assess the existing processes to avoid overlaps and make the best use of the experience accumulated. It also proposed the balance between performance and risk as the metric to measure the quality (or value, adopting the asset management concept) of management decisions. The growing recognition that infrastructures exist in highly complex uncertain contexts requires changing management decisions from choosing the options with the highest expected outcome to the options with the best balance between expected outcome and potential variability of the outcome. Finally, considering sustainability as the ultimate goal, the relation between quality and asset management is linked to the need for integrated infrastructure management by analysing sustainable mobility versus sustainable transport infrastructures.